Knowing how to listen or being willing to listen? A conceptual analysis of active listening - Sainz Palafox, Miguel Angel (2025)
This paper analyzes the concept of active listening from two epistemological perspectives: as a disposition and as a technique, showing that although they are different, they are interrelated and can be either complementary or irreconcilable, depending on the theoretical approach adopted. Active listening as a disposition is related to the internal attitudes of the therapist or facilitator, such as authenticity, empathy, and unconditional acceptance—characteristic of humanistic psychotherapy. This approach values the human encounter and the relationship as ends in themselves. In contrast, active listening as a technique refers to observable behaviors (such as paraphrasing or emotional validation), typical of models focused on problem-solving and behavioral change. From this perspective, active listening is a means to achieve specific goals. The article proposes applying the concept of epistemological vigilance to make a critical and coherent use of active listening, depending on the intention of the intervention process: whether it seeks immediate change or long-term personal development. Finally, it is suggested that active listening, both as a disposition and as a technique, functions as an epistemological affect—that is, as an expression of the professional’s intentions and theoretical foundations. This distinction makes it possible to design intervention strategies that are more consistent with the needs of the context, promoting a reflective use of the concept in educational, therapeutic, and guidance practices.